Chinese students and personal tutorials in a British overseas campus: the strategic choices of emerging adults - Comerio, Giovanna; Walker, James (2021)
Personal tutorials are an essential feature of student support in British universities, therefore they are duplicated on British overseas campuses. It appears that Chinese students are reluctant to seek help when they experience personal difficulties that affect their engagement with learning and their academic performance. Limited literature explores this phenomenon with relevant studies only focusing on Chinese students’ experiences abroad. Furthermore, these studies mainly refer to cultural factors related to traditional Confucianism to explain why these students do not engage with support structures. Drawing on the theory of Emerging Adulthood, this paper analyses the experiences of students on a Chinese branch campus of a British university. A mixed methods research approach was considered the most appropriate means of engaging with the participants; a quantitative study was used in an exploratory fashion to provide unbiased insight into student opinion and experience, and a qualitative content analysis was used to analyse participants’ comments in the open field questions. The findings reveal an alternative portrayal of the “Chinese Personal Tutee”, distant from the traditional Confucian model still predominantly used as an analytical tool in research on Chinese youth. Chinese students on an international campus strategically select their sources of help and prefer to build symmetrical relationships with personal tutors based on personal goals rather than asymmetrical relationships based on ‘care’ provided by adults. Consequently, ‘transnational’ personal tutorial systems pursuing Chinese students’ successful engagement ought to be conceptualised by considering their emerging adulthoods and by respecting their sense of agency.